A Teacher and Parent Consultation Approach to Teaching Toilet training in Early Childhood Children with Special Needs - Anjani Trunoyudho, Etna; Damastuti, Evianti (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
Children with special needs at an early age are children who experience developmental delays. One of the developmental tasks of early childhood is toilet training. Factors that support the success of toilet training are student readiness, cooperation between teachers and parents. Therefore, a consultation approach between parents and teachers is one way that can bridge to equalize perceptions between parents and teachers so that the toilet training program can run at home and school. The purpose of this study is to describe the process of consulting parents and teachers in shaping toilet training in early childhood with special needs. This research uses a qualitative method with a case study approach. Data collection was taken from interviews with parents, class teachers and principals as well as student observations. Data analysis includes steps: data reduction, data presentation, and conclusion drawing. The results showed that the consultation approach to teachers and parents was successful in helping children's toilet training programs both at home and at school.